Temperature effect on dwell-fatigue crack propagation behavior of novel tempered martensitic ferritic steel G115. (1st October 2020) - Tang, Zhengxin; Jing, Hongyang; Xu, Lianyong; Chi, Dazhao; Zhao, Lei; Han, Yongdian; Gao, Yalin
Highlights: da / dN remained constant as increased from 625 to 650 °C for 0-/60-s dwell tests. da / dN increased with increasing temperature for the 600-s dwell tests. FCG has a transgranular cracking mode, regardless of the temperature/load level. CFCG is transgranular at low/high; it is mixed fracture mode at middle. Abstract: The effect of temperature and holding time on the dwell–fatigue crack propagation behavior of a novel tempered martensitic ferritic steel G115 was studied. The crack growth duration greatly increased with the increase in dwell time at all tested temperatures (625–675 °C). The FCG data and the da / dN for the 60-s dwell tests remained nearly constant when the temperature increased from 625 to 650 °C, whereas da / dN increased remarkably when the temperature increased to 675 °C. Moreover, da / dN increased with increasing temperature for the 600-s dwell tests. These results reflect the comprehensive effects of creep, environmental (oxidation) phenomena, and property degradation. In the ( da/dt ) avg versus ( Ct ) avg plot, the crack-propagation data under a specific dwell time fall close to each other, regardless of the temperatures. Scanning electron microscopy observation shows that the fatigue crack propagation has a transgranular cracking mode, regardless of variations in the temperature (625–675 °C) and load level. Meanwhile, the creep-fatigue crack growth mode is transgranular cracking at lower Δ K, whereas it gradually changes to mixed intergranular and transgranular fracture modes with increasing Δ K . The longer the holding time, the more significant the intergranular cracking. The crack growth may change to transgranular mode again when Δ K further increases. The two values of Δ K at which the crack-growth mode change all increase with decreasing dwell time and temperature.